Ibn Hazm on Christianity: An Analysis to His Religious Approaches - Mahmud Ahmad; Mohd Khairul Nizam Zainan Nazri; Mardiana Bt Mat Ishak; Mohd Roslan Mohd Nor; Mohd Yakub Zulkifli Mohd Yusuf; Ishak Suliaman; Khadijah Mohd Khambali Hambali; Mohd Fauzi Hamat (International Digital Organization for Scientific Information (IDOSI), 2024)
Volume 1 No: 4 (page: 242-248)